PENERAPAN SISTEM PEMBEKUAN VAKUM DAN PEMANASAN DARI BAWAH PADA MESIN PENGERING BEKU - Belyamin .; Armansyah H. Tambunan; Hadi K. Purwadaria; M. Idrus Alhamid (Jurnal Keteknikan Pertanian, 2007)
ABSTRACT Freeze drying is the best among the drying methods, especially for high value products. This is due to some reason: minimize tile degradative reaction such as non enzymatic browning, protein denaturizing and enzymatic reaction, little loss of flavor and aroma and high re-absorptivity of solvent. However due to slow drying rate, the drying time is longer and energy consumption is higher, that make freeze drying process expensive. To overcome the problems, drying was proposed to operate by application of vacuum freezing and back heating beside the use of radiation from the upper surface of product. The objective of this research was to prove that freeze drying with vacuum freezing and back heating (PBPVpb) consume less energy than freeze drying with contact plate freezing (PBLS). The research was started by designing and manufacturing a PBPVpb before operating and analyzing it. This research found out that the energy consumption of PBP\/pb was 90.6% of PBLS although the drying time of PBPVpb WaS 29% longer than that of PBLS. The drying rate of PBPVpb was 5 g/h whereas PBLS was 5.6 g/h. Keyword: freeze drying, vacuum freezing, baok heating Diterima: 26 Juni 2007; Disetujui: 19 Agustus 2007